A Changing UK in a Changing Europe: The UK State between European Union and Devolution. Issue 2 (19th May 2016) - Minto, Rachel; Hunt, Jo; Keating, Michael; Mcgowan, Lee
Abstract: Two issues currently dominate the UK's constitutional landscape: the UK's membership of the European Union (EU) on the one hand; and the unsettled constitutional settlements between the UK and the devolved administrations of Scotland, Wales and Northern Ireland on the other. This article considers these two issues in concert. It stresses the distinct relationships between the EU and the devolved territories within the UK—concerning both devolved and non‐devolved policy areas—highlighting the salience of a devolved perspective in any consideration of UK–EU relations. Despite its importance, sensitivity to this has been lacking. The article explores the implications of a 'Leave' or 'Remain' outcome on the future of the internal territorial dynamics within the UK. While there are too many unknowns to be certain of anything, that there will be knock‐on effects is, however, beyond doubt.